Elementary gas‐phase reactions of radical species during chemical vapor deposition of silicon carbide using CH3SiCl3. Issue 5 (11th January 2021) - Sato, Noboru; Funato, Yuichi; Shima, Kohei; Sugiura, Hidetoshi; Fukushima, Yasuyuki; Momose, Takeshi; Koshi, Mitsuo; Shimogaki, Yukihiro
Abstract: We established a kinetic model (the UT2017 model) for chemical vapor deposition of silicon carbide (SiC) from methyltrichlorosilane (CH3 SiCl3, MTS)/H2, and quantitatively identified CH2 SiCl3 as one of the SiC film‐forming species. In a previous study, we established a kinetic model (the UT2014 model), which reproduced the overall decomposition of MTS, but had not validated it in terms of radicals. In the present study, we first validated the UT2014 model by comparing it with the experimental results of radical production from MTS by Lemieux et al, without H2 present. The UT2014 model did not reproduce the production of CH2 Cl from MTS at 1247°C. We found that the reactions of CH2 SiCl3 isomerization to CH2 ClSiCl2 and CH2 ClSiCl2 decomposition to CH2 Cl and SiCl2 were important for the production of CH2 Cl from MTS. We re‐calculated those constants in pressure‐dependent formulas using the Rice‐Ramsperger‐Kassel‐Marcus method at the CBS‐QB3 level. These chemistries were added to the UT2014 model to yield the UT2017 model, which reproduced the production of radicals, including CH2 Cl. Finally, using the UT2017 model, we simulated the gas composition under typical SiC chemical vapor infiltration conditions, which comprised mainly MTS and H2 . A comparison of the simulation results with the partial pressure of film‐forming species in our previous report suggested that CH2 SiCl3 was the possible film‐forming species of SiC from MTS/H2 . For quantitative verification, we estimated the distribution of the partial pressure of CH2 SiCl3 in our reactor while considering the consumption of CH2 SiCl3 on the SiC surface. The values from this simulation result were almost identical to our experimental results for all positions in the reactor. Thus, we showed quantitatively that CH2 SiCl3 is the film‐forming species of SiC.